Character Analysis in The Movie Inside Out Base in Vladimir Propp's Theory - Mujiarni, Umi; Sintia, Dilla; Saputri, Tiara Dwi; Misrita (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This study analyses the characters and narrative structure of the animated film Inside Out (2015) through the lens of Vladimir Propp’s Morphology of the Folktale. While Propp’s theory, originally developed for Russian folktales, identifies thirty-one narrative functions and seven spheres of action in traditional storytelling, this research investigates its applicability to a modern psychological animated film featuring emotion-based characters. The study employs qualitative narrative analysis to map Inside Out’s characters such as Joy, Sadness, Bing Bong, and others, into Propp’s character roles such as hero, helper, donor, and villain, and to identify how the film’s plot aligns with Propp’s narrative functions. Findings reveal that despite the absence of a conventional villain and the abstract nature of its characters, Inside Out effectively mirrors many of Propp’s narrative structures, with Joy’s emotional journey serving as the heroic quest. The study highlights how internal emotional conflicts and symbolic characters can fulfil classical narrative roles, thereby extending Propp’s theory beyond its folkloric origins to contemporary animated storytelling. This study recommends that future research apply Propp’s framework to a broader range of modern films and conduct comparative analyses across traditional folktales and contemporary media to further examine the adaptability of classical narrative models. Additionally, the study suggests the pedagogical use of animated films as effective tools for teaching narrative theory and developing students’ critical analytical skills.